Locally advanced breast cancer: an observational study for the delay in presentation of patients - Shah, Priti; Save, Maitreyee; Khadilkar, Reina; Shah, Pranjal; Kader, Hanaa; Eswarawaka, Mridula (International Surgery Journal, 2020)
Background: Breast cancer is the most common cause of cancer in women and cancer related mortality all over the world. There is strong evidence that delayed diagnosis of breast cancer is associated with poor survival. At our center most of the patients with breast cancer presented as locally advanced breast cancer (LABC) which drew our attention to find out the reasons of delay and its association with different socio-demographic variables. Methods: We enrolled 50 histologically proven cases of LABC in this study. With help of semi structured interview, questions were asked from each patient which could reflect their understanding about the disease to find likely reasons for their delayed presentation, including socioeconomic status. Results: In present study most of our patients were more than 45 years, married. 88% presented late due to unawareness and ignorance about nature and severity of breast cancer disease, 86% had financial issues, 64% had shyness as reason, 20% wasted time by taking alternative treatment, 52% presented late due to painless lump; 30% had fear of losing breast, 18% didn’t get support from family, 4% presented late due to other reasons. Conclusions: Awareness and knowledge of breast cancer was found to be poor amongst sufferers prior to their diagnosis, making it important reason for delayed presentation. Other significant factors being socioeconomic status and education. The need for increased awareness and use of screening practices was identified to be essential for early diagnosis of the disease and for improved outcomes.